Membangun Ketahanan Institusi Keluarga Muslim di Indonesia: Kajian Hukum Perkawinan Islam Menghadapi Tantangan Hegemoni Arus Globalisasi - Chotban, Sippah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The title of this research is "Building the Resilience of Family Institutions in Facing the Hegemony of Globalization Currents from the Perspective of Islamic Marriage Law in Indonesia". This research is library research with the type of data analysis being descriptive-qualitative. The research found that building family resilience amidst the hegemony of globalization is a necessity and a challenge that must be carried out. Moreover, there are also many cases that befall and threaten the resilience of families, both coming from within and from outside. Family resilience has a very important and strategic position in Islamic Marriage Law in Indonesia because family resilience is related to marriage and the purpose of marriage itself. Islamic Marriage Law in Indonesia has its own perspective in building family resilience amidst the hegemony of globalization. This research is expected to provide enriching references as well as scientific insight into Islamic law in answering various problems that often befall and threaten family resilience.